El impacto de las exportaciones de la industria azucarera sobre el PIB del Valle del Cauca entre los años 2018 al 2022 (2023)
The sugar industry of the Cauca Valley is one of the most successful business sectors in Colombia. They are leaders in sugar production, being one of the most productive industrial complexes with the greatest influence on the economic and social development of the region and the country. since it has geographical and crematory conditions that are appropriate for its cultivation and continuous harvest throughout the year, in this way Valle del Cauca is the main department, it has approximately an area of 225,560 hectares planted with sugar cane.